STRATEGI KEPALA PERPUSTAKAAN DALAM MENINGKATKAN MINAT BACA - Ibrahim Ibrahim; Dinda Gita Nazlia (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2023)
This article is entitled Strategy of the Head of Librarians in Increasing Reading Interest in SMP Negeri 3 Banyuasin. The problem that occurs is about the standard of management of education this type of research is qualitative research. This researcher uses descriptive qualitative research method by examining directly to the field. Data collection techniques used are observation, direct interviews with the principal, vice principal, and teachers. The data analysis technique in this study uses data reduction, data presentation, and data verification. The results showed that the standard of library management at SMP Negeri 3 Banyuasin had been carried out well. In terms of increasing interest in reading to students, it has been carried out well, in terms of directing the principal has given direct direction to the head of the library, the principal always coordinates with teachers about strategies to increase students' interest in reading.